Pengembangan Modul Ajar Fisika Berdiferensiasi Berbasis Kurikulum Merdeka - Leni Marlina; Nuriz Dariyani; Ida Sriyanti; Sudirman Sudirman; Meilinda Meilinda (Jurnal Penelitian Pendidikan IPA, 2022)
A differentiated teaching module based on kurikulum merdeka has been successfully developed on measurement materials in good and practical scientific work. The Alessi and Trollip development model, which consists of three stages, was used in this study. These stages are the planning stage, the design stage, and the development stage. During the planning stage, the researcher performed the following tasks: 1) an analysis of the needs of driving school teachers in three districts, namely Banyuasin, OIC, and East OKU, and 2) a diagnostic analysis of student learning styles at SMA Negeri 1 Semendawai Suku III OKU Timur, and 3) observation and analysis of the independent curriculum structure. Following the planning and design stages, researchers conduct alpha and beta tests during the development stage. The Alpha test is used to determine the level of validity of the developed teaching module. Meanwhile, the Beta test is being conducted to determine the practicability of the developed teaching module. The results of the second Alpha test yielded an excellent percentage of 100%. The acceptable rate of the second Beta test results is 100%. Based on the findings of this study, the independent curriculum-based differentiated teaching module on measurement materials in scientific work developed is valid and practical, making it suitable for use in high school physics learning